The dispute between Romania and Ukraine over the deepwater Danube–Black Sea shipping route in the light of the Espoo Convention - Kastory, Agnieszka (Balcanica Posnaniensia. Acta et studia, 2022)
Now the Danube Delta is located on the territory of Ukraine and Romania. In 2002 Ukraine prepared the project of the Danube–Black See deep waterway, which was situated on the arm of Kilia, and one of its branches — Bystre Canal. There were two phases of this project, and each one of them required a separate administrative procedure. Ukraine informed Romania about this project in 2002, and provided an opinion on its impact on the environment in 2004. It was the Espoo Convention violation. Romania launched an investigation procedure against Ukraine. Her compliant was found to be justified. Meeting of the Parties of Espoo Convention took several decisions against Ukraine. The first ordered Ukraine do adapt the provisions to Espoo Convention and to stop work until it was complied with them. Ukraine took advantage of the two phases of project and suspended the second phase, while working on the first one. Subsequent Meetings of the Parties to Espoo Convention noted the half-heartedness and slowness of Ukraine’s action. As a result Ukraine’s work on Danube delta continues to be monitored.